Contributions of Dance in the reduction of Academic Stress in undergraduate students of the Faculty of Medicine of the UNMSM - Asian Canchis, Hugo Enrique (2020)
This article determines the scope of the impact of dance practice on stress, which was developed in 2017 by undergraduate students of the Faculty of Medicine of the Universidad Nacional Mayor de San Marcos. The type of research is based on the quasi-experiment, for which 200 students were tested in each experimental group and control group before and after. The results showed that the control group had significant development The experimental group (experimental group) and the group without the aforementioned experiment (control group). For the study, a survey was designed to identify the variation between the study groups. It is concluded that there is a direct and significant relationship between the variables: "dance practice" and "academic stress" in the students of the Faculty of Medicine of the Universidad Nacional Mayor de San Marcos, presenting a coefficient of significance of 0.05.